The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.cemconres.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of steel fibre reinforced concrete - A literature review

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(101 citation statements)
references
References 59 publications
3
68
0
Order By: Relevance
“…Steel fibers embedded within chloride-contaminated HyFRC were observed to have insignificant corrosion damage, except those fibers located very near a matrix crack or located at the ponding surface itself. Similar observations of the greater chloride threshold required to corrode steel fibers as opposed to conventional steel rebar have been summarized elsewhere in the literature [10,44].…”
Section: Observed Damagesupporting
confidence: 76%
“…Steel fibers embedded within chloride-contaminated HyFRC were observed to have insignificant corrosion damage, except those fibers located very near a matrix crack or located at the ponding surface itself. Similar observations of the greater chloride threshold required to corrode steel fibers as opposed to conventional steel rebar have been summarized elsewhere in the literature [10,44].…”
Section: Observed Damagesupporting
confidence: 76%
“…It has been found that steel fibres have better corrosion resistance than reinforcement bars. This is probably due to there being fewer defects on the fibre surface and a more uniform fibre-matrix interface [27]. However, the long-term corrosion resistance and corrosion behaviour of steel fibres across cracks need further investigation, especially when the crack widths become very large.…”
Section: Residual Sectionmentioning
confidence: 99%
“…Mild steel in concrete is generally believed to be in passive state due to the high alkalinity of the concrete pore solution . However, if reinforced concrete is exposed in a high chloride concentration environment, for example, in seawater, the ingress of chlorides can damage the passive film, triggering pitting and resulting in localized corrosion …”
Section: Resultsmentioning
confidence: 99%